The Validation of the Dai Nippon Medi·Ca SA Method for AOAC Research Institute Performance Tested MethodsSM Certification. (23rd November 2019) - Shimizu, Mai; Takenaka, Kentaro; Suzuki, Takeo; Miyasaka, Aya; Matsuda, Taiki; Iwase, Tatsuhiko; Kyotani, Hitoshi
Abstract: A ready-made dry medium method for Staphylococcus aureus count, the Medi·Ca SA method incubated at 35 or 37°C, was compared with the Baird-Parker method (AOAC Official Method SM 975.55 ) for 11 food matrices: raw beef, raw ground beef, raw lamb, cooked ham, raw salmon, frozen prawn, fresh chilled pasta, pasteurized milk, natural cheese, cream puff, and potato salad. The mean difference between the two methods at each contamination level for each matrix was <0.5 log10, and the 95% confidence intervals on the mean differences fell within the range of −0.50 to 0.50. Standard deviation of repeatability and RSDr values of the Medi·Ca SA method were generally the same level as those of the Baird-Parker method, and r 2 ranged from 0.98 to 1.00. Product consistency and stability studies showed little variability between productions lots and a shelf-life of 16 months. Incubation time within the range of 22–26 h and variations to the sample volume did not adversely affect the results. These results showed that the Medi·Ca SA method is a reasonable alternative to the reference method for selected food matrices and makes it possible to simultaneously detect and enumerate S. aureus in only 24h.